The Influence of Strangulation and Dormancy-Breaking Agent Aplication on Fruit set, Flower and Fruit Drop of Chokun Citrus (Citrus reticulata) - Juliani Hilya; Sakhidin; Djatmiko Heru Adi (BIO Web of Conferences)
Chokun citrus plants (Citrus reticulata) are known for their sweet taste and distinctive aroma. Citrus production in Indonesia fluctuates annually. This research aims to investigate the effects of strangulation and dormancy-breaking agent application on fruiting, flower drop, and fruit drop in Chokun citrus. The study was conducted at the exfarm of Universitas Jenderal Soedirman from July 2023 to January 2024 using a Completely Randomized Design (CRD) with two main treatments: strangulation (without strangulation, single strangulation, double strangulations) and dormancy-breaking agent application (without dormancy breaking agent, KNO3 250 ppm, Etephon 150 ppm), involving a total of 27 citrus trees as research subjects. Strangulation involved wrapping a 1.5 mm diameters wire around the lower stem, which was removed after three months. Dormancy-breaking agents were applied after wire removal. Results indicated that strangulation increased flower and fruit numbers, flower and fruit drop, and leaf carbon content at 32 days after treatment (DAT). Dormancy-breaking agent application did not affect all variables. Interaction between strangulation and dormancy-breaking agents affected flower and fruit numbers, leaf carbon content at 64 DAT, and C/N ratio. This study demonstrates that combining strangulation techniques and dormancy-breaking agent applications can enhance Chokun citrus plant production.